The Diversity and Spatiotemporally Evolutionary Dynamic of Atypical Porcine Pestivirus in China - Ma, Hailong; Li, Wentao; Zhang, Mengjia; Yang, Zhengxin; Lin, Lili; Ghonaim, Ahmed H.; He, Qigai (Frontiers in Microbiology, 2022)
The presence of congenital tremor (CT) type A-Ⅱ in newborn piglets, caused by atypical porcine pestivirus (APPV), has been a focus since 2016. However, the source, evolutionary history, and transmission pattern of APPV in China remain poorly understood. In this study, we undertook phylogenetic analyses based on available complete E2 gene sequences along with 98 newly sequenced E2 genes between 2016 and 2020 in China within the context of global genetic diversity. The phylogenies revealed four distinct lineages of APPV, and interestingly, all lineages could be detected in China with the greatest diversity. Bayesian phylogenetic analyses showed that E2 gene evolves at a mean rate of 1.22 × 10-3 (8.54 × 10-4-1.60 × 10-3) substitutions/site/year. The most recent common ancestor for APPVs is dated to 1886 (1837-1924) CE, somewhat earlier than that the documented emergence of CT (1922 CE). Our phylogeographic analyses suggested that APPV population possibly originated in Netherlands, a country with developed livestock husbandry, and was introduced into China during 1837-2010. Guangdong as a primary seeding population together with Central and Southwest China as epidemic linkers was responsible for the dispersals of APPVs in China. The transmission pattern of “China lineages” (lineage 3 and lineage 4) presented a “south to north” movement tendency, which was likely associated with the implementation of strict environmental policy in China since 2000. Reconstruction of demographic history showed that APPV population size experienced multiple changes, which correlated well with the dynamic of the number of pigs in the past decades in China. Besides, positively selected pressure and geography-driven adaptation were supposed to be key factors for the diversification of APPV lineages. Our findings provide comprehensive insights into the diversity and spatiotemporal dynamic of APPV in China.